Pengaruh Project Based Learning Terhadap Hasil Belajar Materi Kerangka Bangun Ruang Siswa Kelas VI SD Negeri Diwek 1 - Luki Puspitasari; Claudya Zahrani Susilo (Prodi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the effect of the Project-Based Learning model on students` learning outcomes in the spatial framework material for sixth-grade of SD Negeri Diwek 1. The study employed a quantitative approach using a quasi-experimental method with a One- Group Pretest-Posttest design. The participants consisted of 34 students selected through total sampling. Data were collected using learning outcomes tests administered before and after the implementation of the Project-Based Learning model. The collected data were analyzed using descriptive statistics, normality tests (Shapiro-Wilk), paired sample t-test, and effect size analysis. The results showed that the average pretest score was 48.18, while the average posttest score increased to 68.35. The paired sample t-test results indicated a significance value of 0.000 (p < 0.05), which means that there was a significant difference between students` learning outcomes before and after the implementation of the PjBL model. Furthermore, the effect size value obtained was 1.27, which falls into the large category. These findings indicate that the Project-Based Learning model has a strong positive influence on improving students` mathematics learning outcomes, particularly in spatial framework material. Therefore, the Project-Based Learning model can be considered an effective learning strategy to enhance students understanding and engagement in mathematics learning at the elementary school level.